Targeting z-Crystallin by aspirin restores the sensitivity to cisplatin in resistant A2780 ovarian cancer cells - Lulli, Matteo; Trabocchi, Andrea; Roviello, Giandomenico; Catalano, Martina; Papucci, Laura; Parenti, Astrid; Molli, Alice; Napoli, Cristina; Landini, Ida; Schiavone, Nicola; Lapucci, Andrea (Frontiers in Pharmacology, 2024)
Ovarian cancer is the deadliest gynaecologic malignancies worldwide. Platinum based chemotherapy is the mainstay treatment for ovarian cancer; however, frequent recurrence and chemoresistance onset in patients with advanced diseases remain a therapeutic challenge. Although mechanisms underlying the development of chemoresistance are still ambiguous, the B-cell lymphoma-2 (Bcl-2) family is closely associated with chemoresistance in ovarian cancer. We previously disclosed that Zeta-Crystallin (CryZ) is a post-transcriptional regulator of Bcl-2 gene, by binding to Bcl-2 mRNA and increasing its half-life. Here, we investigated the role of CryZ as a novel therapeutic target in A2780 ovarian carcinoma (OV) cells by modulating the protein activity with acetylsalicylic acid (ASA) to restore chemosensitivity. Molecular docking and fragment-mapping based approach revealed potential interaction of ASA within CryZ. Inhibition of CryZ binding to Bcl-2 and Bcl-xl mRNAs by ASA was demonstrated in A375 cells. Cytotoxicity assays were conducted in A2780S/R OV cells to evaluate if CryZ binding activity inhibition and CryZ silencing were able to reverse cisplatin resistance. ASA-treatment determined a downregulation of Bcl-2 and Bcl-xl mRNA levels in A2780S and A2780R cells. ASA-treatment or CryZ silencing were able to increase and restore the chemosensitivity in both sensitive and resistant A2780 ovarian cancer cells, respectively. In this research article we demonstrated that the pharmacological or genetic inhibition of CryZ restores the sensitivity to cisplatin in a model of sensitive or resistant ovarian cancer cells. These findings suggest a new gene-targeted chemotherapeutic approach to restore the cytotoxicity in drug-resistant ovarian cancers and increase the sensitivity in non-resistant cells.